Strategi Indonesia dalam Menghadapi Tirani Perdagangan Bebas - A. K., Syahmin (Indonesian Journal of International Law, 2008)
In Indonesia, the implementation of dumping policy based on the Customs Act Number 10 Year 1995 and its regulation. However, this Act was regarded insufficient, the Indonesian Government therefore created the Import and Repayment Duties of Antidumping Regulation Number 34 Year 1996. This Regulation reffered to the provisions under Article VI of the GATT 1994, which is Multilateral Trade Agreement (MTA) in the GATT/WTO system. To implement the GATT/WTO obligations, on the October 10th 2000, Indonesian Ministry of Industrial and Trade under its Provision Number 427/MPP/Kep/10/2000, established the Indonesian Antidumping Committee (Komite Anti Dumping Indonesia/KADI). This committee responsible to execute the process of acomplishment of Antidumping. Although the Indonesia Government has published a technical guidance for the economic actors to fill out complaint regarding dumping case to KADI, yet a new set of further Antidumping Regulation is needed for certainty of law.